Palm oil waste gasification: the effect of operating temperature for hydrogen production - Ahmad Amirul Asraf, Mohd Daud (2014)
The production of synthesis gas from the gasification of palm oil waste; Kernel Shell, (KS) and Mesocarp Fibre, (MF) has been studied using a small lab scale gasification unit. The effect of operating temperature on the sample for the products yield and composition were investigated. The sample was collected, cleaned, dried, resized and gone through CHNS analysis prior to be used as the feedstock. Initially, approximately three grams of sample was used. Reactor and condenser were weighted before and after the gasification process in order to know the weight percent of solid, liquid and gas for each sample. Nitrogen gas; N2 was first purged at 50 ml/min into the reactor as the carrier gas to remove gases in the system for about 20 minutes. It was done to achieve oxygen free atmosphere in order to avoid any explosion. After that, the flowrate was increased to 100 ml/min and the furnace was turned on to the desired temperature. The products which were syngas and bio-liquid from the gasification were firstly flown into the condenser. Then, the uncondensed gases were flew into a 12 L gas sampling bag and analyzed via Gas Chromatography, GC. The liquid product was trapped in the condenser. The gasification process was done in one hour. The effect of operating temperature has influenced the yield of bio oil, syngas and char for the samples (KS and MF). The highest syngas produced from MF and KS was obtained at 900 oC. As the temperature increased, the product yield of bio-oil and char were decreased. The highest amount of Hydrogen gas produced for both samples was obtained at 900 oC and it can be deduced that 900 oC is the optimum temperature for the gasification process. The composition of the syngas produced was identified using Gas Chromatography (GC). The result showed that the Hydrogen composition in MF is higher than KS. The studies on the production of Hydrogen gas from the gasification of KS and MF showed that the Hydrogen obtained from the KS and MF might be a potential valuable source for renewable fuel and for the usage of chemical feed stocks